1982
DOI: 10.1172/jci110649
|View full text |Cite
|
Sign up to set email alerts
|

Association between colony forming units-granulocyte macrophage expression of Ia-like (HLA-DR) antigen and control of granulocyte and macrophage production. A new role for prostaglandin E.

Abstract: A B S T R A C T The expression of Ia-like antigens on human colony forming units-granulocyte macrophage (CFU-GM) is related to S-phase of the cell cycle, and associated with the control of normal granulocyte and macrophage production by prostaglandin E and acidic isoferritins in vitro. Ia-antigen expression by CFU-GM is lost within 3-6 h of culture at 370C and occurs simultaneously with loss of responsiveness to inhibition by these factors. Culture of bone marrow CFU-GM in a limited exposure suspension culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…In contrast to the effects of PGE 2 on myeloid, erythroid, and multipotential progenitor cell proliferation, [22][23][24][25]34 inhibition of PGE 2 biosynthesis did not affect BrdU incorporation in DC-committed progenitor cells, suggesting that PGE 2 does not primarily regulate DC-lineage progenitor cell proliferation. Because BrdU incorporation measures DNA replication not cell division, we confirmed this finding by in vitro CFDA staining that measures cell division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the effects of PGE 2 on myeloid, erythroid, and multipotential progenitor cell proliferation, [22][23][24][25]34 inhibition of PGE 2 biosynthesis did not affect BrdU incorporation in DC-committed progenitor cells, suggesting that PGE 2 does not primarily regulate DC-lineage progenitor cell proliferation. Because BrdU incorporation measures DNA replication not cell division, we confirmed this finding by in vitro CFDA staining that measures cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to that observed for steady state mice, blockade of PGE 2 synthesis during in vivo Flt3L treatment resulted in significantly reduced DC generation ( Figure 1D). Because DCs develop in the BM from DC lineage-committed HPCs 7,9,16 and we previously demonstrated that PGE 2 can differentially regulate HPCs depending on lineage, [21][22][23][24][25]34 we examined whether the attenuated development of DCs observed on inhibition of PGE 2 biosynthesis results from an effect on the DC-committed progenitor cell compartment. In mice treated with indomethacin for 6 days, the early BM common DC progenitors, CDP (Lin neg c-Kit int Flt3 ϩ CD115 ϩ ; Figure 1E), and immediate cDC precursors, pre-cDC (CD3/CD19/NK1.1/Ter119 neg CD11c ϩ MHCII Ϫ SIRP␣ int Flt3 ϩ ; Figure 1F), were significantly reduced compared with control.…”
mentioning
confidence: 99%
“…5 Using short-term ex vivo pulse exposure of bone marrow cells, similar to exposure strategies previously reported, 6,7 North and colleagues elegantly demonstrated that murine bone marrow transplantation was enhanced by dmPGE 2 . 5 We later demonstrated that this enhanced hematopoietic stem cell (HSC) engraftment resulted from an increase in CXCR4 on hematopoietic stem and progenitor cells and enhanced homing to the marrow; it also increased expression of Survivin, with reduced HSC apoptosis and increased HSC division.…”
Section: Introductionmentioning
confidence: 87%
“…Inhibitory factors, most of which are leukocyte products, include lactoferrin (6), prostaglandin E (7), acidic isoferritin (8), and transferrin (9). In most of the feedback systems described, the Ia (class II) surface antigenic system appears to play a role in the proliferative events in the marrow (10)(11)(12). Both myeloid (colony-forming units granulocytic-monocytic [CFU-GM]) and erythroid progenitor cells (burst-forming units-erythroid and colony-forming units-erythroid [BFU-E and CFU-Ej) express Ta antigenic determinants on their surfaces, although these progenitor cells appear to be generated from pluripotent stem cells lacking Ta antigens (13,14).…”
Section: Introductionmentioning
confidence: 99%